HUBUNGAN DISIPLIN BELAJAR DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN KETERAMPILAN KELAS VIII DI SMP NEGERI 16 PADANG - PERTIWI, INTAN; Zahri, Wildati; Adriani, Adriani (Journal of Home Economics and Tourism, 2014)
This study aimed to describe between the discipline of learning the class VIII student learning outcomes in subjects at Junior High School 16 skills Padang. This research is correlational research. The data obtained through a questionnaire containing statements have been prepared on a Likert scale. The sampling technique is Proportional random sampling. The sample in this study 62 students. Based on the analysis of data description, that the percentage of respondents with a level of achievement indicators include: Time management 56% are in the category of Low, Adherence (compliance) 63% are in categories Low, and Responsibilities 71% are in the Medium category. Variables studied discipline 64% are in the category of Low. Outcome variables studied 46% were in the category of incomplete. The results of the correlation analysis suggests that there is a positive and significant with a correlation of 0.476 relationship between the discipline of learning the class VIII student learning outcomes in subjects at Junior High School 16 skills Padang. Keyword: Discipline of learning, learning outcomes, subjects Skills